LITERATURE CIRCLES IN READING CLASS: STUDENTS’ PARTICIPATION AND PERCEPTION - Novitasari; Eka Listianing Rahayu Rahayu; Bambang Suryanto (University of Muhammadiyah Malang, 2021)
Literature circles are methods to teach reading that aim to bring an enjoyable atmosphere to the class. It refers to a group of students who read the same book and discuss what they have read, with different roles being assigned to each member. It is believed that literature circles can promote the students’ interest and help them get better reading comprehension. Therefore, literature circles are suitable to be implemented in reading classes in higher education. This study aims to investigate the students’ participation and perception towards literature circles in reading class. The research was conducted in reading classes of D3 and D4 English Study Programs of Business Administration Department, State Polytechnic of Malang. The research participants were two classes consisting of 50 students. Questionnaires were used to collect data from the respondents. The data was then analysed using the descriptive quantitative method. The finding shows that the students actively participated in the literature circles and positively perceived it.